Adherence to health protocol after 3 months of emergency responses in community, cafe, and restaurant workers in Yogyakarta City: secondary data analysis of COVID-19 serosurvey in 2020 - Fitriani, Bhekti; Prabandari, Yayi; Indriani, Citra (BKM Public Health and Community Medicine, 2021)
Purpose: The aim of this research was to examine differences in adherence to health protocol between community, cafe, and restaurant workers. Methods: This research employed a cross-sectional design using secondary data from the 2020 COVID-19 serosurvey in Yogyakarta City. The inclusion criterion was respondents aged 19 years and older, while the exclusion criterion was respondents with incomplete data on the variables of interest. Effect size was calculated using the prevalence ratio (PR) derived from bivariate analysis with the chi-square test. Results: Bivariate analysis showed no significant difference in adherence to health protocols between the community and café/restaurant workers (95% CI: 0.99–1.12; p = 0.107). In the community, knowledge was significantly associated with adherence to health protocols (PR: 1.37; 95% CI: 1.19–1.58; p < 0.001). Among café and restaurant workers, both age (PR: 1.18; 95% CI: 1.07–1.29; p = 0.001) and knowledge (PR: 1.13; 95% CI: 1.04–1.24; p = 0.004) were significantly associated with adherence to health protocols. Conclusion: Good knowledge can increase the likelihood of adherence to health protocols among community members, as well as café and restaurant workers. Therefore, education related to COVID-19 prevention should be provided to improve knowledge, especially among young adults.